2019
DOI: 10.1111/epi.14731
|View full text |Cite
|
Sign up to set email alerts
|

SCN2A channelopathies: Mechanisms and models

Abstract: Summary Variants in the SCN2A gene, encoding the voltage‐gated sodium channel NaV1.2, cause a variety of neuropsychiatric syndromes with different severity ranging from self‐limiting epilepsies with early onset to developmental and epileptic encephalopathy with early or late onset and intellectual disability (ID), as well as ID or autism without seizures. Functional analysis of channel defects demonstrated a genotype‐phenotype correlation and suggested effective treatment options for one group of affected pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 64 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…Because primary cultured neurons develop fully functional synapses and are readily accessible, these cells are amenable to image-based screenings and electrophysiological studies making them adequate models to screen for the effects of kinase dysregulation in neurons. We focused on the AIS because this subcellular domain is a key regulator of neuronal excitability and plasticity and many AIS proteins have been linked to neuropsychiatric disorders ( Hsu et al, 2014 ; Carroll et al, 2016 ; Di Re et al, 2017 ; Sanders et al, 2018 ; Wang et al, 2018 ; Hedrich et al, 2019 ; Ortiz-Gonzalez and Wierenga, 2020 ; Reynolds et al, 2020 ). Given the sensitivity of AIS proteins to kinase activity, we determined the effect of kinase inhibition on the subcellular distribution of AIS proteins and found that βIV spectrin was exquisitely sensitive to AKT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Because primary cultured neurons develop fully functional synapses and are readily accessible, these cells are amenable to image-based screenings and electrophysiological studies making them adequate models to screen for the effects of kinase dysregulation in neurons. We focused on the AIS because this subcellular domain is a key regulator of neuronal excitability and plasticity and many AIS proteins have been linked to neuropsychiatric disorders ( Hsu et al, 2014 ; Carroll et al, 2016 ; Di Re et al, 2017 ; Sanders et al, 2018 ; Wang et al, 2018 ; Hedrich et al, 2019 ; Ortiz-Gonzalez and Wierenga, 2020 ; Reynolds et al, 2020 ). Given the sensitivity of AIS proteins to kinase activity, we determined the effect of kinase inhibition on the subcellular distribution of AIS proteins and found that βIV spectrin was exquisitely sensitive to AKT inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models modelling both LoF and GoF mutations in SCN2A have been produced (Hedrich, Lauxmann, & Lerche, 2019). Scn2a KO mice modelling haploinsufficiency were found to display a spectrum of autistic‐like phenotypes such as hyperactivity, anxiety, impaired social and communicative behaviour, as well as cognitive deficits (Lena & Mantegazza, 2019; Middleton et al., 2018; Spratt et al., 2019; Tatsukawa et al., 2019).…”
Section: Neurodevelopmental Disorders With Epilepsy and Epileptic Enc...mentioning
confidence: 99%
“…The transgenic Scn2a Q54 GoF mice exhibits partial and absence‐like seizures with onset at 2 months, as well as stereotyped repetitive behaviours (Kearney et al., 2006). However, while patients with SCN2A encephalopathy do display various types of focal seizures, absence‐like seizures are not commonly reported, suggesting a possible species‐specific effect (Hedrich et al., 2019; Howell et al., 2015).…”
Section: Neurodevelopmental Disorders With Epilepsy and Epileptic Enc...mentioning
confidence: 99%
“…Gain-of-function pathogenic variants of SCN2A underlie the Benign Familial Infantile-Neonatal Seizure (BFNIS) affecting children before three months of age and disappearing with age. Seizures in BFNIS can be controlled with Na + -channel blockers such as phenytoin and carbamazepine, while they are ineffective for the severe form [118,119]. Some BFNIS patients present with EA either co-occurring with epileptic spells [120][121][122][123][124][125] or as the only clinical feature [124][125][126].…”
Section: Scna2mentioning
confidence: 99%